The Value Orientation of Multicultural Islamic Education in the Sipakatau Culture - Muhammad Tang; Yaqub Cikusin; Djunaedy Ghony (International Journal on Advanced Science, Education, and Religion, 2018)
The purpose of this study was to interpret and describe the values ​​of the culture of Sipakatau in the Bugis community to become the foundation for the development of Multicultural Islamic education. The research approach used is qualitative-ethnographic research developed by Gay, Mills, Aurasian & Creswell. Data collection techniques used are in the form of observations, interviews, and documents. Then the data analysis used is a model developed by Miles & Hubermen. After conducting research, it was shown that the cultural values ​​of Sipakatau in Bugis communities in Barang village could be the basis for the development of Multicultural Islamic Education, namely with the concept of "humanizing humans" with the main values, namely; mutual respect and respect, advise each other, support each other and protect, love and love each other, help each other and receive (help and help), and have the same rights before God Almighty.